Assessment of genotypic variability in rice (Oryza Sativa L.) for growth and yield characteristics - M.H.V. BHAVE, GODAWARI S PAWAR, V. PADMA, D. SUBRAHMANYAM S. SUDHEER KUMAR and (The Journal of Research, PJTSAU, 2017)
Crop genotypes play a major role in crop production systems. They affect crop productivity by their higher yield potentials, resistance against insect pest and diseases under different climatic conditions. To evaluate different varieties of rice for their growth and yield characteristics, an experiment was conducted during kharif 2013 and 2014 at ICAR-Indian Institute of Rice Research, Rajendranagar, Hyderabad. Fourty three genotypes from different groups were evaluated in a randomized block design (RBD) with three replications. Data on various growth and yield parameters reveled that the parameters were significantly differed among the genotypes. The mean values for plant height ranged from 87.17 cm to 176.10 cm, leaf area from 718.36 cm2 to 1465.53 cm2, duration for flag leaf emergence varied from 66 to 102 days, duration for 50% flowering from 82 to 119 days, duration for complete growth varied from 107-132 days. Effective tillers per hill varied from 6 to 19, spikelets per panicle from 13 to 65 and grain filling from 54 to 94%. The genotypes with early flowering were found early in maturity thereby showing positive association between these two traits. It was further observed that genotypes with maximum effective tillers produced more grain yield. The grain yield was better in medium plant height coupled with medium maturing lines. Some of the land race varieties are better in grain filling percentage and 1000 seed weight and also in yield, so in future we must pay more attention on land races and they may further tested and utilized in crop improvement programme.